1986
DOI: 10.1016/0149-7634(86)90025-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body temperature after administration of adrenergic and serotonergic agents and related drugs including antidepressants: II

Abstract: This survey continues a second series of compilations of data regarding changes in body temperature induced by drugs and related agents. The information listed includes the species used, the route of administration and dose of drug, the environmental temperature at which experiments were performed, the number of tests, the direction and magnitude of change in body temperature and remarks on the presence of special conditions, such as age or brain lesions. Also indicated is the influence of other drugs, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(18 citation statements)
references
References 473 publications
0
18
0
Order By: Relevance
“…It has been well indicated that NA, and DA play important roles in regulation of the temperature in hypothalamus areas. For example, local injection of NA into PO/AH in rats cause to the increase of the body temperature (Clark & Lipton, 1986) and NA inhibits the activity of heat sensitive neurons in PO/ Ah (Watanabe, Morimoto, & Murakami, 1986). These findings show that NA is involved in the heat production mechanism.…”
Section: Temperature and Central Fatiguementioning
confidence: 65%
“…It has been well indicated that NA, and DA play important roles in regulation of the temperature in hypothalamus areas. For example, local injection of NA into PO/AH in rats cause to the increase of the body temperature (Clark & Lipton, 1986) and NA inhibits the activity of heat sensitive neurons in PO/ Ah (Watanabe, Morimoto, & Murakami, 1986). These findings show that NA is involved in the heat production mechanism.…”
Section: Temperature and Central Fatiguementioning
confidence: 65%
“…Loprinzi et al [48] reported a 50% reduction in hot flashes after 4 weeks of venlafaxine treatment in cancer survivors. These clinical reports investigating the role of SSRIs and SNRIs, our current findings and an extensive body of literature [1,49,50,51,52] suggest that temperature homeostasis is maintained by a delicate interplay between serotonergic and noradrenergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that, compared to amphetamine, the most pronounced serotonergic action of 4-MA could diminish the psychoactive effects of amphetamine leading to the consumption of repeated and higher doses of contaminated amphetamine [2]. Serotonin (5-HT) in the hypothalamus is involved in the regulation of body temperature [6]. Stimulation of 5-HT 2 receptors in hypothalamic neurons mediates hyperthermic effects, whereas stimulation of the 5-HT 1A receptors in these neurons inhibit the endogenous release of hypothalamic 5-HT and leads to hypothermic effects [7,8].…”
Section: Introductionmentioning
confidence: 99%